2021
DOI: 10.1007/s11192-021-04239-9
|View full text |Cite
|
Sign up to set email alerts
|

Why does library holding format really matter for book impact assessment?: Modelling the relationship between citations and altmetrics with print and electronic holdings

Abstract: Scholarly books are important outputs in some fields and their many publishing formats seem to introduce opportunities to scrutinize their impact. As there is a growing interest in the publisher-enforced massive collection of ebooks in libraries in the past decade, this study examined how this influences the relationship that library print holdings (LPH), library electronic holdings (LEH) and total library holdings (TLH) have with other metrics. As a follow up study to a previous research on OCLC library holdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Furthermore, our data does not provide sufficient coverage of electronic holdings. Previous literature has shown that there is a difference between electronic and print holdings (Maleki, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, our data does not provide sufficient coverage of electronic holdings. Previous literature has shown that there is a difference between electronic and print holdings (Maleki, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Not only academic books but also books written for general audiences and books written for professional audiences are an important part of SSH output. Library holdings are associated with various aspects of impact, not only academic impact (citations) but also educational impact (syllabus mentions), cultural impact (White & Zuccala, 2018) or uptake among the general public (Halevi et al, 2016), e.g., in Goodreads (Maleki, 2021). Sivertsen (2022) argues that the SSH interact directly with society through both professional communications (depending on the discipline, these can be commissioned reports, legal commentaries, and textbooks) and public media (including sources of public information and literature aimed at a non-scholarly audience).…”
Section: Books Aimed At General and Professional Audiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the acceleration of the pace of social life and the increase of life pressure, people are more and more inclined to shallow reading, utilitarian reading, entertain-ment reading, fragmented reading, and other reading methods. The traditional reading form based on reading books is undergoing severe challenges [16]. The above shows the importance and value of carrying out national reading promotion activities.…”
Section: Image Retrieval Of Smart Archives From Thementioning
confidence: 99%